PERKEMBANGAN AKUNTANSI BERBASIS AKRUAL PADA SEKTOR PEMERINTAH DI INDONESIA - Riri Zelmiyanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2015)
Under accrual base, revenue and expense are recognized when transaction exist regardless the cashoccur. Accrual base implementation should be carefully, with proper preparation and related structured rules,system, and human resource. Government Accounting Standard (GAS) implementation accrual base will impactthe regulatory changes and accounting system, and must be supported by capacity and capability of humanresources. The implementation of accrual base in Indonesia govermental accounting actually started at 2001with the issuance of MAKUDA. GAS implementation with accrualo base is a mandate of UU No.17/2003 aboutState Finance. However, every unit in government departemen has difference preparation, so GASimplementation based on accrual are done in stages, with the implementation of SAP-based Cash TowardsAccrual based on Government Regulation No. 24 of 2005 and will then move to accrual-based SAP in fullaccordance with Government Regulation No. 71 Year 2010 began the year 2015